Determinant of Money demand in India - Zannah, Mohammmed; Ramly, Ashadi; Mahat, Fauziah (Niali Field Consultancy and Training (NFCT), 2017)
This study empirically examined the Money demand in India to find the stability of money demand between narrow money M1, M2 and Broad money M3 as a prerequisite for achieving sound monetary policy. The monthly data from January 2006 to July 2016 were used for this studies. To determine the relationship between the variables and the stability of the money in India, the study employed Autoregressive Distributed Lag (ARDL) method to analysis the data. The result shows that both narrow (M1, M2) and broad money (M3) are co-integrated with the determinants however it is not significant in long run, except for income as the key factor influences the broad money. Applying CUSUM & CUSUMSQ, the parameter stability test yield that narrow and broad money demand are stable for India.